Interpretação e subjetividade : uma leitura etnográfica de Nove Noites - Santos, Eline Marques dos (2016)
This paper proposes a reflection on the literary reading through an approach that focuses on the process of investigation, that is, this study is concerned with the reader's interaction in his/her interpretative operation. To accomplish this objective, I make use of autoethnography (CLIFFORD, 2008) (GEERTZ, 1973) (SILVA, 2011) (VERSIANI, 2005), a methodological bias that is defined by the analysis of social practices from the intersection of autobiography with ethnography. The adopted perspective helps to reflect on the relevance of the researcher's subjectivity in the construction of interpretation. Here, I use this methodology as a way to analyze the record of my reading process, through the analysis of my journal with daily readings of the novel Nove Noites (2002), by Bernardo Carvalho, observing the various associations established, from critics and readers of the literary text, and even the relation with other texts and personal experiences. For this analysis, I use daily records as an important research source for the registration of the reading process which, for having fragmentation and freedom in writing as features, (LEJEUNE, 2008) (MACHADO, 1998) provides an ideal space for constitution of subjectivities. The theoretical basis also focuses on researchers who reflected on the literary reading, such as Compagnon (2010), Iser (2002; 1979), Jauss (2002), Fish (1992), Culler (1997) and Eco (2002; 2005). This research is still aligned with a perspective that understands the literary reading as a process that allows the construction of the reader’s identities (HALL, 2011) (CULLER, 1999) by the various subjectivities that permeate a literary text.